2008
DOI: 10.1016/j.neuron.2008.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Ikaros Confers Early Temporal Competence to Mouse Retinal Progenitor Cells

Abstract: In the developing mouse retina, multipotent retinal progenitor cells (RPCs) give rise to specific retinal cell types at different times, but the molecular mechanisms regulating how RPCs change over time remain unclear. In the Drosophila neuroblast lineage, the zinc finger transcription factor Hunchback (Hb) is both necessary and sufficient to specify early-born neuronal identity. We show here that Ikaros, a mouse ortholog of Hb, is expressed in all early embryonic RPCs, which then give rise to Ikaros-negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
190
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 206 publications
(205 citation statements)
references
References 55 publications
8
190
2
1
Order By: Relevance
“…In the eye, we consistently found that Ikaros is expressed ubiquitously (Fig. 2C, D), as we reported previously (Elliott et al, 2008). Consistent with widespread Ikaros expression in embryonic tissue, Cremediated recombination did not display any clear tissue-specificity (see Discussion section).…”
Section: Generation Of Ikaros-cre Bac Transgenic Linessupporting
confidence: 89%
See 4 more Smart Citations
“…In the eye, we consistently found that Ikaros is expressed ubiquitously (Fig. 2C, D), as we reported previously (Elliott et al, 2008). Consistent with widespread Ikaros expression in embryonic tissue, Cremediated recombination did not display any clear tissue-specificity (see Discussion section).…”
Section: Generation Of Ikaros-cre Bac Transgenic Linessupporting
confidence: 89%
“…Overall, this expression pattern indicates that both lines A and F express Cre in early progenitor cells, although with different efficiencies. Line A is closer to the apparently ubiquitous Ikaros expression in RPCs at early stages (Elliott et al, 2008), whereas the low subset of Ikaros-positive RPCs achieving Cre-mediated deletion of the reporter in line F leads to sparse arrays of YFP progenies. These expression patterns match what was observed with the b-Gal reporter in these lines.…”
Section: Ikaros-cre Mouse Lines Active In Early Retinal Progenitorsmentioning
confidence: 93%
See 3 more Smart Citations